Potato of foreign breeding varieties’ evalution on resistance to casuative agents of wart Synchytrium endobioticum Schilbersky Percival - Zelia, H.; Sonets, T.; Mykhailyk, S. (Quarantine and plant protection, 2025)
Goal. To determine the reaction of potato cultivars of foreign breeding to infection by Ukrainian pathotypes of the potato wart pathogen for their inclusion in the State Register of Plant Varieties Suitable for Dissemination in Ukraine and for their use in disease-infested areas. Methods. In 2022—2023, 11 foreign potato cultivars were tested: Alverstone Russet, Brook, Euroviva, Cardima, Corazon, Newton, Sunred, Sensation, Spectra, Tiger, and Triple 7. The assessment of potato resistance to the common 1(D1) and aggressive pathotypes of the potato wart pathogen was performed under laboratory conditions at the Ukrainian Research Station for Plant Quarantine of the Institute of Plant Protection, NAAS, on an artificial infectious background in accordance with EPPO Standard PM 7/28/2 and the Methodology for Evaluation and Selection of Potato Breeding Material Resistant to Wart Disease Synchytrium endobioticum (Schilb.) Perc., harmonized with EU requirements. Field trials were also conducted in areas of pathogen distribution. Results. All studied cultivars were evaluated as resistant to the common pathotype of the pathogen. Potato cultivars resistant to aggressive pathotypes were identified: — 11(M1) — Mizhhirya: Alverstone Russet, Euroviva, Cardima, Sunred, Tiger; — 13(R2) — Rakhiv: Alverstone Russet, Euroviva, Cardima, Corazon, Sunred, Triple 7; — 22(B1) — Bystrets: Alverstone Russet, Euroviva, Cardima, Sunred, Spectra. Only two cultivars — Corazon and Tiger — were selected as resistant to the aggressive pathotype 18(Ya) — Yasynia. The potato cultivars Brook and Sensation were susceptible to all four aggressive pathotypes of the pathogen. Conclusions. The selection of potato cultivars resistant to D1 — the common pathotype of the wart pathogen — was the most effective. These cultivars have been included in the State Register of Plant Varieties Suitable for Dissemination in Ukraine. Potato cultivars that showed a negative reaction to infection by aggressive pathotypes of the wart pathogen are recommended for use in disease-infested areas.